2013
DOI: 10.1016/j.contraception.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The creeping pearl: why has the rate of contraceptive failure increased in clinical trials of combined hormonal contraceptive pills?

Abstract: BACKGROUND Despite several drawbacks, the Pearl Index continues to be the most widely used statistical measure of contraceptive failure. However, Pearl indices reported in studies of newer hormonal contraceptives appear to be increasing. STUDY DESIGN We searched PubMed and MIS databases for prospective trials evaluating oral contraceptive (OC) efficacy to examine potential factors that could contribute to increasing Pearl indices. RESULTS Numerous potential factors were identified, including an increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 33 publications
(49 reference statements)
1
51
0
1
Order By: Relevance
“…1 Median unscheduled bleeding and/or spotting and bleeding alone days per 91-day cycle (a) and per patient-month (b) during treatment with Seasonique Ò in adult women (n = 1006) in a 1-year, noncomparative, multicentre, phase III trial [21] endometriosis, iron deficiency and anaemia, and in others, monthly bleeding is an inconvenience that interferes with quality of life and productivity [3,5]. Additionally, it has been postulated that an extended-cycle OC may help to avoid missing first pills, which is a cause of pill failure and unintended pregnancy [27]. In a 1-year, noncomparative trial of healthy, sexually active women, Seasonique Ò was found to have acceptable efficacy for the prevention of pregnancy in terms of the Pearl index for the overall (typical use) and method-failure (compliant use) pregnancy rates (Sect.…”
Section: Dosage and Administrationmentioning
confidence: 97%
See 2 more Smart Citations
“…1 Median unscheduled bleeding and/or spotting and bleeding alone days per 91-day cycle (a) and per patient-month (b) during treatment with Seasonique Ò in adult women (n = 1006) in a 1-year, noncomparative, multicentre, phase III trial [21] endometriosis, iron deficiency and anaemia, and in others, monthly bleeding is an inconvenience that interferes with quality of life and productivity [3,5]. Additionally, it has been postulated that an extended-cycle OC may help to avoid missing first pills, which is a cause of pill failure and unintended pregnancy [27]. In a 1-year, noncomparative trial of healthy, sexually active women, Seasonique Ò was found to have acceptable efficacy for the prevention of pregnancy in terms of the Pearl index for the overall (typical use) and method-failure (compliant use) pregnancy rates (Sect.…”
Section: Dosage and Administrationmentioning
confidence: 97%
“…Moreover, regulatory agencies have differing requirements for the calculation of the Pearl index [27]. For example, the US FDA calculated the Pearl index for Seasonique Ò as 1.77, based on 7 pregnancies that occurred on-treatment over 5125.…”
Section: Dosage and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently two methods are used for measuring contraceptive efficacy: the Pearl Index and the life table. Despite several drawbacks, the Pearl Index continues to be the most widely used statistical measure of contraceptive failure 17. It is defined as the number of failures per 100 woman-years of exposure 18.…”
Section: What Is Zoely?mentioning
confidence: 99%
“…The Pearl Index for COCs is estimated at 0.3–4.0. The life table analysis provides the contraceptive failure rate for each month of use and can provide a cumulative failure rate for any duration of exposure 17. The failure rate with perfect use (true pill failure) is 0.1% and with typical use (user and method failure), it is closer to 5% 18.…”
Section: What Is Zoely?mentioning
confidence: 99%